Unveiling the reality: the toll of labor rights exclusion on Banishanta’s sex workers - Sarbomangala, Kongka (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Social Science in Anthropology, 2023.